THE EFFECT OF E-FORM IMPLEMENTATION ON TAX COMPLIANCE MEDIATED BY USER SATISFACTION - Azizah, Faridah Nur (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2026)
This study aims to analyze the effect of e-form implementation on tax compliance, with user satisfaction as a mediating variable. E-form implementation is measured through system quality, service quality, information quality, convenience, and reduction in compliance costs. This research employs a quantitative approach and was conducted on 99 individual taxpayers engaged in business and/or freelance activities registered at the Jakarta Setiabudi Satu Tax Office. Data were collected using questionnaires and analyzed using multiple linear regression and Hayes’ PROCESS Macro with SPSS version 29. The results indicate that system quality, service quality, and reduction in compliance costs have a significant positive effect on tax compliance, while information quality and convenience have a significant negative effect. Furthermore, user satisfaction significantly mediates the relationship between convenience and tax compliance but does not mediate the relationships between the other e-form implementation variables and tax compliance. User satisfaction itself has a significant positive effect on tax compliance. These findings imply that regular education on the importance of reporting tax returns through e-forms should be conducted by the Jakarta Setiabudi Satu Tax Office and that continuous improvement of e-form features should be prioritized by the Directorate General of Taxes to enhance taxpayer compliance.